Rigorous solution of a mean field spin glass model. (2000) - Dorlas, T. C.; Wedagedera, J. R.
Abstract : A separable spin glass model whose exchange integral takes the form J i j = J ( ξ i 1 ξ j 2 + ξ i 2 ξ j 1 ) which was solved by van Hemmen et al. [12] using large deviation theory [14] is rigorously treated. The almost sure convergence criteria associated with the cumulant generating function C ( t ) with respect to the quenched random variables ξ is carefully investigated, and it is proved that the related excluded null set 𝒩 is independent of t . The free energy and hence the other thermodynamic quantities are rederived using Varadhan's Large Deviation Theorem. A simulation is also presented for the entropy when ξ assumes a Gaussian distribution.